A Novel Low-Cost Bio-Sorbent Prepared from Crisp Persimmon Peel by Low-Temperature Pyrolysis for Adsorption of Organic Dyes - Xie, Lu-Qing; Jiang, Xin-Yu; Yu, Jin-Gang (Molecules (Basel, Switzerland), 2022)
In order to properly reuse food waste and remove various contaminants from wastewater, the development of green, sustainable and clean technologies has demonstrated potential in the efficient inhibition of secondary pollution to the environment. In this study, an economical and green method was used to prepare biochar from crisp persimmon peel (CPP) using flash-vacuum pyrolysis at different temperatures (200–700 °C; referred to as CPP200–CPP700). CPP200 has high polarity, low aromaticity and high oxygen-containing functional groups that exhibit superior MB adsorption capabilities. CPP200 that was prepared at a relatively low temperature of 200 °C exhibited a high adsorption capacity of 59.72 mg/g toward methylene blue (MB), which was relatively higher than that for alizarin yellow R (4.05 mg/g) and neutral red (39.08 mg/g), indicating that CPP200 possesses a higher adsorption selectivity for cationic dyes. Kinetics investigation revealed that the kinetic data of CPP200 for the adsorption of MB was better fitted by a linear pseudo-second-order model. Isothermal studies indicated that the linear Langmuir model was more suitable for describing the adsorption process. The adsorption thermodynamics illustrated that the adsorption of MB onto CPP200 was spontaneous and endothermic. EDS and IR analyses of CPP200 for both pre- and post-adsorption of MB showed that electrostatic interactions between oxygen-containing groups on biochar and target MB dominated the adsorption procedure, in addition to hydrogen bonding interactions. Reusability tests confirmed the excellent regeneration characteristics of CPP200, indicating that CPP200 may be used as a green, sustainable, highly efficient and recyclable adsorbent for the selective removal of cationic organic dyes.